2007
DOI: 10.1007/s10616-007-9078-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recombinant M-CSF production in CHO cells by glycerol addition: model and validation

Abstract: Addition of stimulatory chemical such as glycerol was found to increase recombinant protein production in Chinese hamster ovary (CHO) cells. However, glycerol influenced cell mitosis and reduced cell growth rate. We developed a controlled proliferation strategy to utilize the stimulation of glycerol on recombinant protein production and mitigate the problem of growth inhibition. The approach is to apply a two-stage process, where cells are cultured without glycerol for a period of time in order to obtain enoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…Similarly, we observed improvements to cell viability from glycerol, both as a main effect and in combination with glucosamine and galactose. These observations are novel, and contrast with other reports, which have seen improved specific productivity, but also growth inhibition above 1.0% of glycerol, 36 and enhanced sialylation levels and greater product yield due to reduced aggregation. 23…”
Section: Univariable Findingscontrasting
confidence: 91%
See 1 more Smart Citation
“…Similarly, we observed improvements to cell viability from glycerol, both as a main effect and in combination with glucosamine and galactose. These observations are novel, and contrast with other reports, which have seen improved specific productivity, but also growth inhibition above 1.0% of glycerol, 36 and enhanced sialylation levels and greater product yield due to reduced aggregation. 23…”
Section: Univariable Findingscontrasting
confidence: 91%
“…Numerous media additives have been used to modulate glycosylation structures, including galactose, glucosamine, 15,19 N-acetyl glucosamine (GlucNAc), uridine, mannose, N-acetyl neuraminic acid (NeuNAc), 16 N-acetyl mannosamine (ManNAc), 17,18 ammonia, 19 manganese, 20 dolichol phosphate, 21 cytidine, 22 and glycerol. 23,36 Similarly, a variety of enzyme inhibitors has been exploited. [24][25][26][27] In our study, we tested 10 commonly used media additives and characterized their effect on the glycosylation profile of different IgG1 molecules.…”
Section: Univariable Findingsmentioning
confidence: 99%
“…It was reported that the addition of, e.g., DMSO, glycerol, or sodium butyrate can enhance the production of biopharmaceuticals in different mammalian cells (Liu and Chen 2007;Oh et al 2005;Rodriguez et al 2005;Cherlet and Marc 2000). Despite an increase in specific productivity in many producers, treatment with these chemicals results usually in a reduced growth rate that can reduce the final product titer compared to untreated cells (Rodriguez et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Such enhancers should meet the following requirements: (a) be safe for operators and patients, (b) maintain the quality of the final product, (c) be cost-effective, and (d) be easy to handle. With these requirements in mind, the following enhancers have been suggested: butyrate (De Leon Gatti et al 2007;Jiang and Sharfstein 2008;Mimura et al 2001;Oh et al 1993Oh et al , 2005, caspase inhibitor (Arden et al 2007), carnosine (Yegorov et al 2007), glycerol (Liu and Chen 2007), nucleosides (Carvalhal et al 2003), linoleic acid (Butler et al 1999), lipopolysaccharide (Martin-Lopez et al 2007, dimethyl sulfoxide (Ling et al 2003;Tsao et al 2001), rapamycin (Balcarcel and Stephanopoulos 2001), retinoic acid (Inoue et al 2000), sericin (Terada et al 2002), spermine (Miyazaki et al 1998), various sugars (Coroadinha et al 2006), valproic acid (Backliwal et al 2008;Konno et al 2006), and vitamin A (Inoue et al 1999) (summarized in Table 1). …”
Section: Introductionmentioning
confidence: 99%